(untitled) (Voice of Teacher, 2025)
This paper explores how Nepali dohori songs function as sites for the narrative reconstruction of sorrow (dukkha), hope (asa), and collective consciousness (chetana) to highlight socio-political and cultural significance. The purpose of the paper is to outline how those dialogic folk songs, performed as improvised exchanges between male and female singers, articulate personal grief, social injustice, and political aspiration to foster shared emotional and moral awareness. Employing a qualitative method, the paper integrates textual analysis of songs, performance observation, and critical engagement with cultural theory, Gramsci’s hegemony, and subaltern studies to trace individual and collective experiences. The analysis demonstrates that Dohori songs reflect emotional, social realities and raise counter-hegemonic voices to challenge dominant narratives. Findings reveal that the songs’ interplay of sorrow and hope cultivates ethical reflection, political consciousness, and communal solidarity. The dialogic structure embodies expressing voices and relationality. Ultimately, Nepali dohori emerges as a culturally grounded pedagogy of emotion, where personal expression, historical memory, and collective aspiration converge to enable audiences to engage in transformative reflection and envision possibilities for social justice and political transformation.